Factors Affecting the Quality of Human Resources in Civil Servants (Case Study of the National Disaster Management Agency) - Komaruddin Simanjuntak; Madhakomala Madhakomala; Kazan Gunawan (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
This research was conducted to improve the quality of human resource management in Civil Servants (especially employees of the National Disaster Management Agency). This study examines the effect of transformational leadership, human capital, and innovative work behavior on quality human resource management. This study used a sample of 239 employees of the National Disaster Management Agency. The analytical method used is SEM analysis with WrapPLS. This research shows that only human capital and innovative work behavior can have a positive and significant effect on quality human resource management. The findings of this study prove that transformational leadership has no significant effect on quality human resource management and innovation work behavior. Further research has been described in this study.